Can child restraint product information developed using consumer testing sustain correct use 6 months after child restraint purchase? Study protocol for a cluster randomised controlled trial. Issue 3 (7th March 2018) - Brown, Julie; Elkington, Jane; Hall, Alexandra; Keay, Lisa; Charlton, Judith L; Hunter, Kate; Koppel, Sjaan; Hayen, Andrew; Bilston, Lynne E
Abstract : Background: With long-standing and widespread high rates of errors in child restraint use, there is a need to identify effective methods to address this problem. Information supplied with products at the point of sale may be a potentially efficient delivery point for such a countermeasure. The aim of this study is to establish whether product materials developed using a consumer-driven approach reduce errors in restraint use among purchasers of new child restraint systems. Methods: A cluster randomised controlled trial (cRCT) will be conducted. Retail stores (n=22) in the greater Sydney area will be randomised into intervention sites (n=11) and control sites (n=11), stratified by geographical and socioeconomic indicators. Participants (n=836) will enter the study on purchase of a restraint. Outcome measures are errors in installation of the restraint as observed by a trained researcher during a 6-month follow-up home assessment, and adjustment checks made by the parent when the child is placed into the restraint (observed using naturalistic methods). Process evaluation measures will also be collected during the home visit. An intention-to-treat approach will be used for all analyses. Correct use and adjustment checks made by the parent will be compared between control and intervention groups using a logistic regression model. The number of installation errors between groups will be compared using Poisson regression. Discussion: This cRCT will determine the effectiveness of targeted, consumer-driven information on actual error rates in use of restraints. More broadly, it may provide a best practice model for developing safety product information. Trial registration number: ACTRN12617001252303p; Pre-results.